Labour in the suburbs : political change in Croydon during the twentieth century - Tichelar, Michael (New York, NY : Routledge, 2023)
"This book is the first comprehensive economic, social and political study of the London suburb of Croydon from 1900 up to the present day. Labour in the Suburbs will be of interest to the general reader as well as students of modern British history with special interests in electoral sociology, political representation and suburbanisation. It provides a template against which to measure the process of suburbanisation in the UK and internationally"--
Introduction. Changing definitions of suburbia -- From 'dunroamin' to 'edge city' -- A new typology of different suburbs -- Edwardian socialism (1900-1914) -- New patterns of citizenship and politics (1914 -1939) -- Affluence and dealignment (1939-1979) -- Black settlement and new politics (1979-1997) -- Peace and disarmament -- Housing and redevelopment -- Conclusion. Towards an edge city (1997 -- 2020).
Keywords: Labour Party (Great Britain) -- History; Political parties -- Great Britain -- History; Suburbanites -- Political activity -- England -- London; Political participation -- England -- London; Political culture -- England -- London; Croydon (London, England) -- Politics and government; Croydon (London, England) -- Social conditions; HISTORY / Europe / Great Britain; HISTORY / Modern / General; HISTORY / Social History